Study on ultrashort pulse propagation in single-mode fiber - Xu, Yingchu (Nanyang Technological University, 2023)
The ultrashort optical pulse which has sub-picosecond pulse width and high peak power has versatile potential applications across diverse fields such as material science, biomedical imaging, and optical communication. Hence, lasing of the ultrashort pulse has become increasingly important. The fiber-based lasing system has many advantages. For example, compared to free space setup, the fiber system is more robust because no constant beam alignment is needed. Also, the small size of the fiber allows it to miniaturize the lasing system. To investigate the ultrashort pulse lasing based on fiber, it is necessary to study how the ultrashort pulse travels in single-mode fiber (SMF) and fiber lasing systems. Therefore, the objective of this project is to numerically simulate the ultrashort pulse propagation in SMF and fiber cavities which allows mode-locking. The simulation is based on solving the nonlinear Schrödinger equation (NLSE) using the symmetric split-step Fourier method (SSFM). The simulation results illustrated the linear and nonlinear effects which distort the pulse shape and spectrum during propagation. Also, the dissipative soliton solution simulated in the passively mode-locking fiber cavity demonstrated the great potential for ultrashort pulse lasing in fiber. The ultrashort high-power laser will have tremendous effects on high-speed communication, high-resolution bioimaging, and molecule spectroscopy.